Strategi Komunikasi Pemasaran Wisata Nagari Koto Hilalang, Solok, Sumatera Barat - Yulia Sariswaty S; Dini Rahmawati; Rina Dwi Handayani; Yunika Komalasari (Jurnal Pariwisata Terapan, 2018)
Nagari Koto Hilalang is one of potential tourist villages in Solok Regency, West Sumatera Province. This area has beautiful landscape, traditional houses of Minang as heritage and hundreds years old of ancient artefacts as well as lifestyle of local community that still keeps socio-culture system and unique local wisdom. Those potentials have not been exploited, managed and developed to the maximum by the local government and community up to now. This research aimed to arrange the concept of marketing communication strategy for Nagari Koto Hilalang in Kubung Subdistrict, Solok Regency, West Sumatera Province to attract tourists’ interest.